UIN Ponorogo Students’ Preferences in Using BSI Mobile Application Services - Misbahul Lucky Keysa Setiawan; Iza Hanifuddin (Institut Agama Islam Negeri Ponorogo, 2025)
Introduction: This study investigates the preferences of UIN Ponorogo students in using the BSI Mobile application, a digital service from Bank Syariah Indonesia. The increasing relevance of mobile banking in students’ daily financial transactions highlights the importance of understanding user preferences and satisfaction. Research Methods: The research employed a qualitative field study approach. Data were collected through questionnaires from 40 respondents and in-depth interviews with 12 students across various faculties. Results: The findings reveal that most students are satisfied with the convenience and practical features of BSI Mobile, such as interbank transfers, bill payments, and mobile top-ups. However, some users expressed concerns regarding incomplete features and technical issues. Key factors influencing preferences include ease of access, compliance with Islamic principles, and peer recommendations. BSI Mobile significantly contributes to fulfilling students’ banking needs. Nevertheless, improvements are still needed, particularly in application reliability and feature enhancements. Conclusion: These insights are expected to guide the development of more user-centric, Sharia-compliant mobile banking services.